2012
DOI: 10.1590/s2237-93632012000300012
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesia for hemorrhoidectomy with bilateral pudendal blockade on an ambulatory patient: a controlled clinical study

Abstract: Imbelloni LE; Vieira EM; Carneiro AF. Postoperative analgesia for hemorrhoidectomy with bilateral pudendal blockade on an ambulatory patient: a controlled clinical study. J Coloproctol, 2012;32(3): 291-296. ABSTRACT: Background and objectives:Reducing postoperative pain in hemorrhoidectomy is still a challenge. This prospective, randomized, double-blind study was conducted to compare bilateral pudendal blockade with peripheral nerve stimulator to relieve postoperative pain with the method commonly used. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 18 publications
1
34
0
Order By: Relevance
“…Moreover, the mean time for first rescue analgesia was 14 hours in the PNB group, and it was 4 hours in the SA group. These results were similar to previous studies reporting that PNB had a longer analgesic effect than local infiltration [ 5 , 13 ]. In order to prolong the duration of PNB and provide better postoperative analgesia, dexmedetomidine was added as an adjuvant to the ropivacaine.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the mean time for first rescue analgesia was 14 hours in the PNB group, and it was 4 hours in the SA group. These results were similar to previous studies reporting that PNB had a longer analgesic effect than local infiltration [ 5 , 13 ]. In order to prolong the duration of PNB and provide better postoperative analgesia, dexmedetomidine was added as an adjuvant to the ropivacaine.…”
Section: Discussionsupporting
confidence: 92%
“…In theory, PNB enables analgesia or anesthesia of the perineal region. Previous studies reported that PNB can provide excellent postoperative analgesia for hemorrhoids surgery [5,9,[11][12][13][14]. e PNB was recommended for all patients undergoing hemorrhoidal surgery by PROSPECT (PROcedure-SPECific postoperative pain managemenT) Working Group [15].…”
Section: Introductionmentioning
confidence: 99%
“…Fourteen randomized trials with a total of 1214 patients were included in the present meta-analysis. 31–44…”
Section: Resultsmentioning
confidence: 99%
“…Inclusion criteria were well defined by all studies, whereas 4 did not specify the exclusion criteria. 32,33,39,40 Seven studies were double-blinded, 31,32,34,36,40,41,44 one was single-blinded 35 and the other did not qualify for either.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation